Template-induced self-activation route for nitrogen-doped hierarchically porous carbon spheres for electric double layer capacitors. (September 2018) - Guo, Hongshuai; Ding, Bing; Wang, Jie; Zhang, Yadi; Hao, Xiaodong; Wu, Langyuan; An, Yufeng; Dou, Hui; Zhang, Xiaogang
Abstract: The synthesis of highly nitrogen-doped hierarchical carbon spheres (NPCS) is reported. The NPCS with pomegranate-like nanostructure were prepared by the CaCO3 spheres template-induced self-activation route with dopamine as the carbon precursor. The template-induced self-activation mechanism was carefully investigated by controlling experiment conditions and thermogravimetric analyses combined with mass spectrometry. Under the optimized conditions, the as-prepared NPCS demonstrate large specific area (up to 1984 m 2 g −1 ) and high level of nitrogen (N, 7.57%) doping. Electrochemical evaluations indicate that the energy density of NPCS-based EDLC devices can reach 6.2 and 14.4 Wh kg −1 in 6 M KOH electrolyte and aqueous concentrated electrolyte (5 M LiTFSI), respectively. This work provides a novel approach for preparing nanoporous carbon materials with hierarchical porosity and well-defined nanostructure. Graphical abstract: Image 1